2015
DOI: 10.1016/j.pcad.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction and Lung Capillary Injury in Cardiovascular Diseases

Abstract: Cardiac dysfunction of both systolic and diastolic origin leads to increased left atrial pressure, lung capillary injury and increased resistance to gas transfer. Acutely, pressure-induced trauma disrupts the endothelial and alveolar anatomical configuration and definitively causes an impairment of cellular pathways involved in fluid-flux regulation and gas exchange efficiency, a process well identified as stress failure of the alveolarcapillary membrane. In chronic heart failure (HF), additional stimuli other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 66 publications
1
13
1
Order By: Relevance
“…25 In this study population, although EAC showed a positive relationship with blood TKB level and PCWP, the blood TKB level did not show a significant direct relationship with PCWP. PCWP, an indicator of pulmonary congestion, might be associated with EAC through the blood-gas barrier, in addition to the increased blood ketone body level in HF.…”
Section: Discussioncontrasting
confidence: 55%
“…25 In this study population, although EAC showed a positive relationship with blood TKB level and PCWP, the blood TKB level did not show a significant direct relationship with PCWP. PCWP, an indicator of pulmonary congestion, might be associated with EAC through the blood-gas barrier, in addition to the increased blood ketone body level in HF.…”
Section: Discussioncontrasting
confidence: 55%
“…30,37 Impairment of Na,K-ATPase function appears to be a hallmark during lung injury even in a preclinical stage. 30,35,38 In our study, we demonstrated that MaR1 not only increased Na,K-ATPase expression in rat lung tissues and primary ATII cells after LPS challenge by western blotting, immunohistochemistry, and confocal laser-scanning microscopy measurement, but also upregulation of Na,K-ATPase activity in vivo. Altogether, our data from the lung tissues and cell culture indicate that MaR1 promotes AFC through both of the essential mechanisms of ENaC and Na,K-ATPase.…”
Section: Discussionsupporting
confidence: 49%
“…Repetitive or severe decompensations may result in cardiopulmonary remodelling (i.e. endothelial dysfunction, proliferation of myofibroblasts, fibrosis and thickening of the extracellular matrix) with an impairment in alveolar gas diffusion properties, pulmonary vasoconstriction and, finally, pulmonary hypertension . This process also leads to the restrictive ventilation pattern observed in CHF .…”
Section: Organ Systems Impacted By Congestion In Acute Heart Failure:mentioning
confidence: 99%